Crises and the pandemic effect on smart destinations - Arpaci, Suat (Emerald Group Publishing Ltd., 2024)
The tourism sector is one of the fastest growing sectors in recent years according to the World Tourism Organization. In recent years, there have been an increasing number of disasters and crises. There are many factors affecting the tourism sector, from natural events to human impact. Tourism sector has suffered great damage from national and global crises. The Gulf War in 1991, the tsunami disaster in 2004, the global economic crisis in 2009 and the pandemic in 2019 can be given as examples of events that negatively affected tourism. The tourism sector in the world has faced the pandemic, which is the biggest global shock in recent times. This situation reinforces the need for tourism businesses and stakeholders to be prepared for crisis and pandemic. With the globalization of the tourism industry and the world becoming more interdependent and interconnected, it is a fact that crises occurring in one part of the world can affect tourism activities in a wider area or worldwide. Since tourism is not at the top of peoples list of needs, it is one of the first plans that tourists will change and cancel as soon as they perceive a threat to themselves. Therefore, the tourism sector is highly sensitive to crises and pandemics. In the face of crisis sensitivity, the tourism sector is also very skillful in eliminating the effects of the crisis as soon as possible. In this study, the impact of crisis and pandemic on the destination in the tourism sector will be explained with examples from some crisis and pandemic cases, and the requirements of tourism enterprises for crisis and pandemic preparedness will be underlined. © 2024 Alhamzah Alnoor, Gül Erkol Bayram, Chew XinYing and Syed Haider Ali Shah. All rights reserved.